By the sea - Gurnah, Abdulrazak (London Bloomsbury, 2002)
In the late afternoon of November 23rd, Saleh Omar arrives at Gatwick Airport with a small bag in which lies a mahogany box containing incense - and little else. He used to own a furniture shop, his own house, and be a husband and father. Now he is an asylum seeker from paradise, claiming silence as his only protection.
Keywords: Tanzanians--England--Fiction.